Lady Dicks and Lesbian Brothers : Staging the Unimaginable at the WOW Cafe Theater - Davy, Kate (Book collections on Project MUSE., 2010)
"Out of a small, hand-to-mouth, women's theater collective called the WOW Cafe located on the lower east side of Manhattan, there emerged some of the most important theater troupes and performance artists of the 1980s and 1990s, including the Split Britches Company, the Five Lesbian Brothers, Carmelita Tropicana, Holly Hughes, Lisa Kron, Deb Margolin, Reno, Peggy Shaw, and Lois Weaver. The WOW (Women's One World) Cafe Theatre appeared on the cultural scene at a critical turning point in both the women's movement and feminist theory, putting a witty, hilarious, gender-bending and erotically charged aesthetic on the stage for women in general and lesbians in particular. The storefront that became the WOW Cafe Theatre saw dozens of excitingly original and enormously funny performances created, performed, and turned over at lightning speed--a kind of "hit and run" theater. As the demands on the space increased, the women behind WOW organized as a collective and moved their theater to an abandoned doll factory where it continues to operate today. For three decades the WOW Cafe has nurtured fledgling women writers, designers, and performers who continue to create important performance work. This book provides a critical history of this avant-garde venture whose ongoing "system of anarchy" has been largely responsible for its thirty-year staying power, after dozens of other women's theaters have collapsed. WOW artists were creating a wholly original cultural landscape across which women could represent themselves on their own terms. Parody, cross-dressing, zany comedy, and an unbridled eroticism are hallmarks of WOW's aesthetic, combined--importantly and powerfully--with a presumptive address to the audience as if everyone onstage, in the audience, and in the world is lesbian. The author's research included in-depth interviews with WOW veterans; newspaper reviews of the earliest productions; and rare, unpublished photographs. The book also includes a chronology of productions that have highlighted WOW's performance schedule since the early '80s."--Publisher